Augmented Humans Conference 2023
DOI: 10.1145/3582700.3582727
|View full text |Cite
|
Sign up to set email alerts
|

Affective Umbrella – A Wearable System to Visualize Heart and Electrodermal Activity, towards Emotion Regulation through Somaesthetic Appreciation

Abstract: Figure 1: Affective Umbrella: Somaethestic appreciation through heart activity (light intensity change) and electrodermal activity (number of peaks influence the color) for augmenting emotion regulation in the real world using an umbrella. Dashed line circles illustrate the virtual effect of the device in action around the user.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Eye tracking-for attention recognition and state detection, by assessment of some parameters [15], e.g., pupil dilation [16,17], saccade and fixation duration [18]; • Facial expression recognition-for emotional and cognitive state detection [19][20][21]; • Electrocardiography (ECG), electrodermal activity (EDA) [22][23][24][25][26], and skin temperature sensors [27]-for assessment of the human body's physiological reactions related to stress, anxiety, agitation, cognitive load, etc. It was also shown that the detection of heart rate variability could be based on photoplethysmography (PPG) sensors integrated into wearable devices [28,29], as well as on traditional electrode-based technology integrated into plasters [30] or smart textiles [31,32]; • Electroencephalography (EEG) [33][34][35][36][37][38]-for capturing the cognition processes, even in cases of a lack of behavioral reaction caused by a specific stimulus.…”
mentioning
confidence: 99%
“…Eye tracking-for attention recognition and state detection, by assessment of some parameters [15], e.g., pupil dilation [16,17], saccade and fixation duration [18]; • Facial expression recognition-for emotional and cognitive state detection [19][20][21]; • Electrocardiography (ECG), electrodermal activity (EDA) [22][23][24][25][26], and skin temperature sensors [27]-for assessment of the human body's physiological reactions related to stress, anxiety, agitation, cognitive load, etc. It was also shown that the detection of heart rate variability could be based on photoplethysmography (PPG) sensors integrated into wearable devices [28,29], as well as on traditional electrode-based technology integrated into plasters [30] or smart textiles [31,32]; • Electroencephalography (EEG) [33][34][35][36][37][38]-for capturing the cognition processes, even in cases of a lack of behavioral reaction caused by a specific stimulus.…”
mentioning
confidence: 99%